Application of a New Efficient Normal Parameter Reduction Algorithm of Soft Sets in Online Shopping - Ma, Xiuqin; Hongwu, Qin (World Academy of Science, Engineering and Technology, 2014)
A new efficient normal parameter reduction algorithm of soft set in decision making was proposed. However, up to the present, few documents have focused on real-life applications of this algorithm. Accordingly, we apply a New Efficient Normal Parameter Reduction algorithm into real-life datasets of online shopping, such as Blackberry Mobile Phone Dataset. Experimental results show that this algorithm is not only suitable but feasible for dealing with the online shopping.